Magnetostratigraphy: A Summary - Herman Darman; Edy Sunardi (Ikatan Ahli Geologi Indonesia, 1998)
Magnetostratigraphy is the element of stratigraphy that deals with the magnetic characteristics of rock units, obtained by measuring the direction and intensity of magnetism in rocks of different ages. The magnetic characteristic most often used, however, is the polarity of magnetic remanence. The polarity is said to be